Penerapan Sistem Absensi Sekolah Menggunakan Fingerprint Terintegrasi Dengan Smartphone Android - A Sumarudin; Willy Permana; Adi Suheryadi; Kikis Maulana; Noufal Ibrahim (Journal of Applied Informatics and Computing, 2019)
The need of student attendance information in schools is a major factor in success of the academic process. Often there are validation and identification errors in the student attendance process (human error or manipulation process) as well as the slowness of information obtained, since the attendance is recorded manually in each class. This has an impact on success of the academic process directly and the community at large. Because the importance of attendance information, various studies have offered the system in the process of student attendance, with various technologies. One popular technology and believed to be validating and identifying well is the fingerprint. Therefore, this paper proposes the introduction of attendance system in schools by utilizing fingerprint technology integrated with android smartphone so that information can be delivered quickly. This study use Fingerprint X-100C as a means of identification of student data at the time of absence then the attendance data will be sent to the system database by SOAP (Simple Object Access Protocol) Web Service. The system will validate and transmit that information on the android Smartphone via the newly created XML Service. The success rate of this system in processing absence reach around 90,47% with delay time of sending information 0.0024 s This system has been tested and applied to SMK N 1 Indramayu.